2010
DOI: 10.1266/ggs.85.31
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of mitochondrial transcriptome in germinating wheat embryos and seedlings subjected to cold, salinity and osmotic stresses

Abstract: Mitochondrial functions are potential targets of abiotic stresses that are major environmental factors limiting plant development and productivity. To evaluate mitochondrial responses to abiotic stresses we studied mitochondrial transcriptome profiles at the early stages of wheat development after imbibition under normal and induced stress conditions. Three stresses given were low temperature (4°C), high salinity (0.2 M NaCl) and high osmotic potential (0.3 M mannitol). All these stresses greatly reduced growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 60 publications
0
15
0
1
Order By: Relevance
“…2010). In embryonic axes of lotus ( Nelumbo nucifera ) exposed to LT (4 °C) for 48 h the MnSOD gene was induced eightfold (Naydenov et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2010). In embryonic axes of lotus ( Nelumbo nucifera ) exposed to LT (4 °C) for 48 h the MnSOD gene was induced eightfold (Naydenov et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Raphanus sativus, the mitochondrial Mn-SOD gene expression was strongly induced by osmotic stress, moderately induced by phytohormones such as ABA and IAA, and not induced by xenobiotics other than cercosporin (Kwon and An, 2003). In wheat seedlings exposed to several types of stress (low temperature, salinity, and osmotic stress), the mitochondrial Mn-SOD transcript was induced (Naydenov et al, 2010), indicating that changes in mitochondrial redox capacity can provoke overexpression at the transcriptional level of nuclear genes encoding mitochondrial antioxidant proteins, as in the case of Mn-SOD. These data contrast with findings in other plant species, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier microarray analysis of mitochondrial gene expression at the early stage of wheat shoot tissues reported that the ccm FN gene showed increased transcript level under three different stress conditions, low temperature (4°C), high salinity (0.2 M NaCl) and high osmotic potential (0.3 M mannitol) [48]. …”
Section: Discussionmentioning
confidence: 99%